Membangun Karakter Pancasila Melalui Pembelajaran Sejarah Berbasis Proyek di SMA - Naredi, Hari; Ruslan, Ahmad; Pratama, Cahya Adhitya (CHRONOLOGIA, 2025)
This study discusses efforts to develop Pancasila character through project-based history learning at the Senior High School (SMA) level as a solution in the learning process. The purpose of this research is to examine how project-based history learning can foster Pancasila character in high school students. Using a qualitative approach with a literature study method, this research collects and analyzes various sources related to character education, the implementation of Pancasila values, and project-based learning methods in history subjects. The results show that history learning designed contextually and student-centered can cultivate Pancasila values such as mutual cooperation, tolerance, nationalism, and responsibility. By involving students in real-life-oriented historical projects, they not only understand historical events but also reflect the nation's noble values in their daily lives.